Pengaruh Independensi Auditor, Remote Audit, dan Disiplin Kerja Terhadap Kinerja Auditor di Kantor Akuntan Publik (KAP) Jakarta Pusat - Muhammad Dhava Aditya; Ati Sumiati; Dwi Kismayanti Respati (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to examine the effect of auditor independence, remote audit, and work discipline on auditor performance at Public Accounting Firms (KAP) in Central Jakarta. The research highlights the importance of maintaining auditor integrity and the increasing adoption of remote audit technology in the digital era. A quantitative approach was applied using an online questionnaire distributed to 100 external auditors from 15 Public Accounting Firms. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) and regression analysis with the help of SmartPLS software. The results indicate that auditor independence, remote audit, and work discipline have a positive and significant effect on auditor performance, both partially and simultaneously. These findings suggest that auditor performance depends not only on technical competence but also on professional attitude, technological adaptation, and discipline. The study supports the Agency Theory and Expectancy Theory as theoretical foundations explaining the link between motivation, responsibility, and auditor performance.